Pengaruh Proporsi Ekstrak Daun Kersen (Muntingia calabura Linn) dan Ekstrak Daun Sirsak (Annona muricata Linn) terhadap Aktivitas Antioksidan dan Daya Terima Yoghurt - Husna, Zulhidayatil; Syainah, Ermina (Jurnal Kesehatan Indonesia, 2024)
Background: Indonesia ranks first with the most cancer cases in Southeast Asia. Degenerative diseases such as cancer occur due to the induction of free radicals, substances that can counteract and prevent damage caused by free radicals are called antioxidants. Objectives:To determine the effect of the proportions of kersen leaf extract and soursop leaf extract on the antioxidant activity and acceptability of yogurt. Methods: This research is experimental with a true experimental design (posttest with control group design). This research consists of 2 stages. The first stage, namely the introduction, aimed to determine the proportion of kersen leaf extract and soursop leaf extract that were most widely accepted/preferred by panelists from the 5 treatments given (P1 = 100 ml:0 ml, P2 = 75ml:25 ml, P3 = 50ml:50 ml, P4 = 25 ml:75 ml, P5 = 0ml:100 ml). The second stage or main research aims to determine the chemical quality (antioxidant activity) in the selected treatment. Results: The results of the organoleptic test showed that all hedonic categories, namely aroma, color and taste except for texture, had significant differences at p <0.05. The best proportion was obtained in the P2 treatment, namely the proportion of 75ml DK : 25ml DS. The P2 treatment increased the antioxidant activity of yogurt, which was 52.33ppm compared to the control yogurt, which had an antioxidant activity of 73.78ppm. Conclusions: There is an effect of the proportion of kersen leaf extract and soursop leaf extract on the antioxidant activity and acceptability of yogurt except texture.